Towards becoming a property owner in the city: From being displaced to becoming a citizen in urban DR Congo. (June 2019) - Jacobs, Carolien; Ruhamya Mugenzi, Joachim; Lubala Kubiha, Stanislas; Assumani, Innocent
Highlights: Three distinct stages can be discerned in sustainable local settlement. Legal tenure security is not a guarantee of de facto tenure security. Owning a house in town improves tenure security (a bit) and social status (a lot). Who owns a plot in the city, belongs to the city. In absence of the rule of law, real tenure security is difficult to achieve. Abstract: Sustainable local settlement in the area of refuge is considered one of the durable solutions to displacement, but not so much is known about ways in which internally displaced persons (IDPs) self-settle in urban settings. Based on two qualitative research projects carried out amongst IDPs in an urban setting in the conflict-affected east of the Democratic Republic of Congo (DRC), this paper explores the main stages of settlement of IDPs, ranging from being hosted to becoming a formal owner of a plot. Combining theoretical perspectives from refugee studies and land studies, the paper investigates to what extent the different stages of settlement bring tenure security to IDPs. Policy often assumes that formal ownership is desirable as it provides tenure security and subsequently economic investment opportunities. Our data show that even formal ownership does not provide adequate tenure security when the rule of law is lacking and that obtaining 'access' to a property is more critical than obtaining rights. Yet, IDPs nevertheless continue to aspire ownership that is as formal as possible. We argue that this is related to the social status of ownership that helps to transform somebody from an outsider that does not belong in the city to a resident that is entitled to claim her/his right to the city and benefit from the advantages that come with belonging to urban space. There is thus a strong mutual relationship between social status and connections on the one hand and tenure security and access to housing on the other hand that feed into people's sense of belonging.